Reading the “Outsider Within”: Counter-Narratives of Human Rights in Black Women’s Fiction - Shane McCoy (Radical Teacher, 2015)
In Pedagogies of Crossing (2005), M. Jacqui Alexander asserts that human rights are not rights at all; in fact, human rights does little to mitigate the violence perpetuated by late capitalism and the legacies of imperialism and colonialism. Alexander’s point of contention brings to bear the fact that the passing of human rights by the United Nations, among other groups, institutes a “dominant knowledge framework” that does nothing to mitigate the violence perpetuated by unequal power structures (2005; 124). My paper focuses on the function of literary counter-narratives as a useful pedagogical strategy for teaching about human rights in the undergraduate classroom. I frame my analysis within the theoretical debates in critical pedagogy and turn to what Stephen Slemon defines as the “primal scene of colonialist management”—the literary studies classroom—in order to examine the ways in which contemporary black women’s writing problematizes the rhetoric of ‘women’s rights as human rights.’ Despite the common belief that white middle-class readers are consuming ‘exotic’ literature when reading immigrant fiction, as noted by scholars Kanishka Chowdhury (1992) and Inderpal Grewal (2005), I maintain that counter-narratives are useful for intervening in the reproduction of a “patriotic education” (Sheth 2013) that undergirds rights-based discourse, in general, and human rights, in particular, as desirable global policies that mitigate the violence of social injustices. Through primary texts Michelle Cliff’s Abeng (1984), Jamaica Kincaid’s Lucy (1990), and Chimamanda Ngozi Adichie’s Americanah (2013), I argue that these texts perform a counter-“cultural technology” in teaching about human rights in literary studies through the lens of “race radicalism” (Melamed 2011), that is cultural production that interrupts the totalizing effects of neocolonial and imperial discourses so often produced in dominant Western literature. Cliff, Kincaid, and Adichie strategically produce oppositional “outsider” narratives that trouble the hegemonic narrative of ‘women’s rights as human rights,’ which implicitly positions women of color in a subordinate position (Mohanty 1986; Spivak 1986).  As black feminist Patricia Hill Collins notes, the “‘outsider within’ status has provided a special standpoint on self, family, and society for Afro-American women.” This standpoint is especially productive for “producing distinctive analyses of race, class, and gender.” I extend Hill Collins’ concept to also include the category of ‘nation.’ Simply put, I argue that the counter-narratives produced by these writers make privy the position of the cultural outsider to American students who have “taken-for-granted assumptions” of human rights discourses as cultural insiders in the U.S. With insight drawn from critical pedagogy, I construct a counter-curriculum that intervenes in a reproduction of global human rights policies constructed through neoliberal ideologies.